Isolation of four Exoparasites species Dacctylogyrous extensus, D.minutus, Gyrodactylus elegans, Cryptobia branchialis in Cyprinus carpio farms in Lattakia (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2025)
The current study aimed at investigating the exoparasites in Cyprinus carpio farms. Samples were collected monthly from three farms in Lattakia (Salah Al-Din Dam, 16 Tishreen) as well as a private farm in Deir Hanna. The skin, mouth cavity, nostrils and gills of all individuals were examined.In this study, four exoparasites species were isolated,  Dactylogyrus minutus, D.extensus, Gyrodactylus elegans, Criptobia branchialis. The resultes revealed differences in prevalence and intensity of isolated spescies in the three farms studied. So, the highest prevalence  of D.minutus was recorded in the private farm (75%) with an intensity of 3.03 parasite/fish, while the highest prevalence  of  D.extensus was recorded in Salah AL- Din Dam farm (68%) with an intensity of 3.11. However, G.elegans has been only recorded in the private farm with a prevalence of 45% and an intensity of 3.61.This study is the first that  isolate  Criptobia branchialis in C.carpio gills in Syria.
Keywords: Key words: Cyprinus carpio, Exoparasites, Dactylogyrus sp, Gyrodactylus sp, Cryptobia